Experimental phasing for structure determination using membrane‐protein crystals grown by the lipid cubic phase method. (1st January 2015) - Li, Dianfan; Pye, Valerie E.; Caffrey, Martin
<x xml:space="preserve">Abstract</x> Despite the marked increase in the number of membrane‐protein structures solved using crystals grown by the lipid cubic phase or in meso method, only ten have been determined by SAD/MAD. This is likely to be a consequence of the technical difficulties associated with handling proteins and crystals in the sticky and viscous hosting mesophase that is usually incubated in glass sandwich plates for the purposes of crystallization. Here, a four‐year campaign aimed at phasing the in meso structure of the integral membrane diacylglycerol kinase (DgkA) from Escherichia coli is reported. Heavy‐atom labelling of this small hydrophobic enzyme was attempted by pre‐labelling, co‐crystallization, soaking, site‐specific mercury binding to genetically engineered single‐cysteine mutants and selenomethionine incorporation. Strategies and techniques for special handling are reported, as well as the typical results and the lessons learned for each of these approaches. In addition, an assay to assess the accessibility of cysteine residues in membrane proteins for mercury labelling is introduced. The various techniques and strategies described will provide a valuable reference for future experimental phasing of membrane proteins where crystals are grown by the lipid cubic phase method.